Study of redox behavior of Cu(II) and interaction of Cu(II) with lysine in the aqueous medium using cyclic voltammetry - Gomaa, Esam Arafa; Negm, Amr; Tahoon, Mohamed Abdel Khalek (European Journal of Chemistry, 2016)
Potassium chloride (0.1 M) and acetate buffer of different pH are used to study the redox behavior of Cu(II) ions in absence and presence of lysine amino acid. The potential window +1500 mV and -1000 mV was used to study the redox properties at solid glassy carbon electrode. Silver/silver chloride is used as a reference electrode and the counter electrode used is Pt. One pair of cathodic and anodic peaks for the Cu(II)/Cu(0) system is showed in cyclic voltammograms indicating the presence of two-electron transfer. The interaction between metal and ligand is supported by the shift of peak potential and charge transfer rate constant (ks) values. Concentration effect of Cu(II) ions and solution pH effect on the interaction was also studied. The quasi-reversible process is indicated by a higher value of peak current ratio and peak potential separation (ΔE).